2020
DOI: 10.1002/bdr2.1661
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low‐dose chlorpyrifos on neurobehavior and potential mechanisms: A review of studies in rodents, zebrafish, and Caenorhabditis elegans

Abstract: Objectives Exposure to chlorpyrifos (CPF), a neurotoxic insecticide, is implicated with adverse neurodevelopmental effects in children through noncholinergic mechanisms. Methods This review presents qualitative and quantitative evidence in three animal models (rodent, zebrafish, and Caenorhabditis elegans), for neurodevelopmental and behavioral effects occurring at CPF doses lower than those inhibiting acetylcholinesterase (AChE). Results CPF treatment in rodents at low noncholinergic doses during neurodevelop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 220 publications
(444 reference statements)
0
21
0
Order By: Relevance
“…Organophosphates' primary reported MoA, especially for acute neurotoxicity, is inhibition of acetylcholinesterase (AChE). However, behavioral studies in rodents, zebrafish and C. elegans suggest adverse effects of organophosphates on brain development after perinatal exposure already below concentrations inhibiting AChE, yet with some uncertainties (Silva 2020). Specific mechanisms for organophosphate-induced DNT in general have not been identified.…”
Section: Organophosphatesmentioning
confidence: 99%
“…Organophosphates' primary reported MoA, especially for acute neurotoxicity, is inhibition of acetylcholinesterase (AChE). However, behavioral studies in rodents, zebrafish and C. elegans suggest adverse effects of organophosphates on brain development after perinatal exposure already below concentrations inhibiting AChE, yet with some uncertainties (Silva 2020). Specific mechanisms for organophosphate-induced DNT in general have not been identified.…”
Section: Organophosphatesmentioning
confidence: 99%
“…Both human and rodent studies have found interesting links between exposure to these various pesticides and ASD diagnosis or ASD-like behaviors [ 24 , 25 ]. However, results differ depending on the agent, the dose, the time of exposure, age of behavioral assessment, and the outcomes measured.…”
Section: Introductionmentioning
confidence: 99%
“…Sex differences in this study can be attributed to various factors that require further investigation (reviewed in [72]. ASD is more common in males than in females [73,74], as observed in some genetic mouse models of the disorder [66].…”
Section: Discussionmentioning
confidence: 89%